Thinking globally, acting locally: Women activists’ accounts - Alldred Pam (Temida)
This paper intends to describe the range of forms women’s resistance to globalisation takes, emphasising diverse strategies from everyday acts, the development of practical alternative resources, organising in women’s groups or trades unions, mass demonstrations and symbolic defiance. Recognising that it is the women of the South, in particular, who bear the brunt of the impact of neoliberal ‘free market’ economic policies, it hoped to be sensitive to the struggles for survival that might frame the urgency of resistance amongst women of the South, and make links with some of the strategies of activist women in the more privileged North.